Atrial fibrillation screening on systematic ambulatory electrocardiogram monitoring after percutaneous patent foramen ovale closure: A prospective study - Florence Leclercq (Elsevier, 2021)
Background: Increased risk of new-onset atrial fibrillation (AF) after patent foramen ovale (PFO) closure was observed in randomized trials without however systematic AF screening. We aimed to evaluate the incidence of AF within 6-month following PFO closure with serial 24-hour ambulatory electrocardiogram (AECG) monitoring. Methods: All patients undergoing PFO closure were prospectively included in 2 centers. AF was defined as irregular rhythm without discernible P waves > 30 s on AECG at day 0, 1-month and 6-month follow-up. Primary endpoint was the incidence of AF within the study period. Secondary endpoints evaluated clinical outcomes within 6-month follow-up. Results: Between February 2018 and March 2019, 62 patients underwent PFO closure including 40 male (64.5%) with a mean age of 48 ± 9.5. Atrial septal aneurysm was observed in 37 patients (64.9%), 57 patients (91.9%) received an Amplatzer Occluder device (Abbott Vascular) and 5 (8.1%) an Occlutech device (Occlutech). After a mean follow-up of 7.7 ± 2.8 months, new-onset AF occurred in 3 patients (4.8%), all within the first month following PFO closure, including one per-procedural, all were asymptomatic and paroxysmal. Two patients with AF (3.2%) required chronic oral anticoagulant therapy. No adverse outcomes occurred at follow-up. No predictive factors of AF were highlighted. A total of 16 patients (25.8%) reported palpitations without AF on the AECGs. Conclusion: In highly selected patients, incidence of AF, evaluated with 3 systematic 24-hour AECG within 6-month following PFO closure, was low (<5%). Always paroxysmal, AF occurred within the first month after the procedure and was not associated with adverse outcomes.